Inventory - Andrew Leach (Footprint)
What is the value, now, in conducting historical research into architectural ideas? The paper addresses the function of contemporary PhD research in light of a) the so-called historiographical turn in architectural history, theory and criticism research consolidated in the last decade or so; b) the broader positions in which critical and historical knowledge and practices are implicated within present-day architectural culture; and c) the particular circumstances of PhD research in architecture in Australian universities. It revisits a paper written in 2005 that constructs the PhD in architecture as a space of authorized release from the burdens of habitual knowledge within the architecture discipline, accountable both to disciplinary knowledge and a broader architectural culture represented most obviously by the architecture profession. In light of the positions it explores and contemporary circumstances, it will consider the question of how legitimacy of subject is construed and defended for the doctorate in architectural history.